IMPROVEMENT OF PENSION INSURANCE PRINCIPLES - Yu. Makarenko; N. Kuryacha (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. The article presents basic principles of investments into pension funds, namely, the principles of safety, profitability and negotiability, and specific features of pension insurance in the world, such as administration of premium collection, features that are specific for rural areas and specific features of «ethical investing». It was proved that the countries that developed pension systems of a new type should use the experience of guaranteed pension payments. To overcome the financial crisis in pension provision system, it is necessary to develop new principles for renovation of the world pension markets. It was found out that use of the pay-as-you-go pension system is a vital issue for many countries on the back of the financial crisis and failure of citizens to make pension contributions.